Repression of Cell Proliferation by miR319-Regulated TCP4 - Schommer, Carla (2014)
Leaf development has been extensively studied on a genetic level. However, little is known about the interplay between the developmental regulators and the cell cycle machinery—a link that ultimately affects leaf form and size. miR319 is a conserved microRNA that regulates TCP transcription factors involved in multiple developmental pathways, including leaf development and senescence, organ curvature, and hormone biosynthesis and signaling. Here, we analyze the participation of TCP4 in the control of cell proliferation. A small increase in TCP4 activity has an immediate impact on leaf cell number, by significantly reducing cell proliferation. Plants with high TCP4 levels have a strong reduction in the expression of genes known to be active in G2-M phase of the cell cycle. Part of these effects is mediated by induction of miR396, which represses Growth-Regulating Factor (GRF) transcription factors. Detailed analysis revealed TCP4 to be a direct regulator of MIR396b. However, we found that TCP4 can control cell proliferation through additional pathways, and we identified a direct connection between TCP4 and ICK1/KRP1, a gene involved in the progression of the cell cycle. Our results show that TCP4 can activate different pathways that repress cell proliferation